The anorexic effect of DL-fenfluramine is dependent on animals' habituation to different food types - Yi, Sun Shin; Choi, SuJean (Frontiers in Integrative Neuroscience, 2022)
Background: As rates of obesity and diabetes have dramatically increased over the past decades, the use of anti-obesity drugs has become a routine therapeutic measure. However, the pharmacologic effects of chronic use of these drugs in humans often result in a reduced efficacy in reducing appetite and body weight through mechanisms that have yet to be identified. An example of this can be found in animal studies that are chronically treated with the appetite suppressant dl-fenfluramine (FEN), which its tolerance develops in animals and humans. In most studies, the appetite effects of FEN in animal studies are typically measured by feeding changes in a balanced standard diet. To determine whether FEN differentially alters appetite suppression in animals with long-term expression with different macronutrient diet compositions, we measured the anorexic effects of FEN specifically in male rats that had previously been chronically maintained on normal chow (NC) or a high fat and carbohydrate western diet (WD). Methods: Three experiments were conducted by habituating the animals’ diet by giving either NC or WD for a month. Animals maintained on NC or WD were subsequently offered both diet options ad libitum over either a 2-day or 7-day adaptation period while receiving daily systemic FEN treatment. Results: The results suggested that the long-term habituated food affected the food preference of animals and appetite even after chronic systemic FEN administration. Therefore, the effectiveness and success of the failure of chronic repeated anti-obesity drug use may be dependent on habituated food type. Conclusion: It was found that the appetite suppressant effect could be determined by the palatability of a specific macronutrient and habituated food rather than a change in the concentration of administered FEN. This result is a critical study on the reason for taking medication considering the patient’s past dietary habits for successful weight loss.